Development of Bacterial Leaflets as a Means of Educating High School Students class X SMA PGRI 1 Ploso - Mega Mufidatul Saputri; Ospa Pea Yuanita Meishanti; Mucharommah Sartika Ami (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The river is a gathering place for water, water quality is greatly influenced by human activities. One of the causes of river water pollution is the presence of domestic waste. This can lead to pollution of water due to microorganisms, s ne of one of her are bacteria Coliform. Coliform bacteria are microorganisms that are usually used as indicators in determining whether a water source is contaminated by pathogens or not. Konto River is a river in East Java originating from the mountains of Argowayang-Anjasmoro Malang. Media is part which can’t be separated from the learning process. In the 2013 curriculum, bacteria material is listed in Basic Competencies (KD) 3.5 and 4.5. Leaflet media for river water quality test that will be developed in this research.